The Role of Social Marketing Campaign in Increasing Public Awareness of Bringing Drinking Bottle - Lisdayanti, Annisa; Dewi, Elsa (International Journal of Psychosocial Rehabilitation, 2020)
Bandung is a city famous for creativity in various fields, including culinary. The culinary category with quite high growth is in the beverage industry. The impact of the increased processed beverage industry is the increase in plastic waste. In an effort to reduce plastic waste, it is necessary to have public awareness to work to reduce plastic waste, one of the efforts that can be done by bringing drinking bottles every day. In increasing public awareness, it is necessary to have a social marketing campaign. The calculation of the sample used in the study is to use iteration; the calculation results are carried out 3 times, and the results obtained are 116 respondents. The research design uses descriptive and verification, and the research method used is multiple regression. The results showed that the social marketing campaign had an influence on the decision to bring bottles to the community, with a simultaneous effect value of 63.8%, and the rest was influenced by other variables not examined in this study.